2018
DOI: 10.1108/ijoem-05-2017-0171
|View full text |Cite
|
Sign up to set email alerts
|

Is government borrowing crowding out long term debt resources

Abstract: Purpose The purpose of this paper is to empirically investigate the possibility of financial crowding out in the long-term debt market in India taking the corporate bond market as a proxy. Design/methodology/approach The study follows a two-pronged approach. First, it tests the corporate bond market sensitivity to interest rate, along with other determinants like commercial bank credit and government securities size using the autoregressive distributed lag approach. These are considered instrumental in the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
2
8
1
Order By: Relevance
“…Therefore, model 6 was used as the regression model. The above contradicts the findings of a previous study by Hasnat and Ashraf (2018), which showed that the bond market is very sensitive to the interest rate. The above results suggest that the interest rate is not an important factor for the retail investor.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Therefore, model 6 was used as the regression model. The above contradicts the findings of a previous study by Hasnat and Ashraf (2018), which showed that the bond market is very sensitive to the interest rate. The above results suggest that the interest rate is not an important factor for the retail investor.…”
Section: Resultscontrasting
confidence: 99%
“…According to research, tax incentives can play a critical role in mobilizing retail savings for sustainable growth projects in India (Harikumar & D, 2017). Tax-free bonds are also considered risk-free because government-backed entities issue them and, therefore, the bond market is led by the government securities (Hasnat & Ashraf, 2018). Thus, the hypothesis proposed is as follows:…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…This attempt helps businesses maintain sustainability (Abosag and Lee, 2013;Signori et al, 2019). Besides, for firms' sustainability, especially, in the Indian context, it appears that both the purchasers and the corresponding upstream suppliers have given much importance to developing a stable and robust dyadic relationship among stakeholders (Dholakia et al, 2018;Hasnat and Ashraf, 2018;. This would help to achieve competitive advantages and to ensure benefits derived from enhancing the relationship.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between public and private investment is also conditional on the features of the legal and economic system. In developing countries, large fiscal deficits may trigger an increase in the interest rate (Hasnat and Ashraf, 2018), which can have an adverse impact on private investment. However, if the fiscal deficit is induced by well-targeted public investment, the crowding-out effect can be dampened or eliminated.…”
Section: Introductionmentioning
confidence: 99%